Knockout of ENO1 leads to metabolism reprogramming and tumor retardation in pancreatic cancer - Song, Qingru; Zhang, Kai; Sun, Tianjiao; Xu, Congcong; Zhao, Wei; Zhang, Zhiqian (Frontiers in Oncology, 2023)
The shift in glucose utilization from oxidative phosphorylation to glycolysis is the hallmark of tumor cells. The overexpression of ENO1, one of the key enzymes in the glycolysis process, has been identified in several cancers, however, its role in pancreatic cancer (PC) is yet unclear. This study identifies ENO1 as an indispensable factor in the progression of PC. Interestingly, ENO1-knockout could inhibit cell invasion and migration and prevent cell proliferation in PC cells (PANC-1 and MIA PaCa-2); meanwhile, tumor cell glucose uptake and lactate excretion also decreased significantly. Furthermore, ENO1-knockout reduced colony formation and tumorigenesis in both in vitro and in vivo tests. In total, after ENO1 knockout, 727 differentially expressed genes (DEGs) were identified in PC cells by RNA-seq. Gene Ontology enrichment analysis revealed that these DEGs are mainly associated with components such as the ‘extracellular matrix’ and ‘endoplasmic reticulum lumen’, and participate in the regulation of signal receptor activity. Kyoto Encyclopedia of Genes and Genomes pathway analysis revealed that the identified DEGs are associated with pathways, such as ‘fructose and mannose metabolism’, ‘pentose phosphate pathway, and ‘sugar metabolism for amino and nucleotide. Gene Set Enrichment Analysis showed that ENO1 knockout promoted the upregulation of oxidative phosphorylation and lipid metabolism pathways-related genes. Altogether, these results indicated that ENO1-knockout inhibited tumorigenesis by reducing cell glycolysis and activating other metabolic pathways by altering the expression of G6PD, ALDOC, UAP1, as well as other related metabolic genes. Concisely, ENO1, which plays a vital role in the abnormal glucose metabolism in PC, can be exploited as a target to control carcinogenesis by reducing aerobic glycolysis.